Serious Games to Enhance Digital Competencies Acquisition for Training Faculty - Sandí Delgado, Juan Carlos (2019)
This study investigates and analyzes the strengths of educational games to enhance the acquisition of digital skills capabilities among faculty. Through a bibliographic review, a comparative analysis of the main characteristics of a series of educational games selected according to the analysis criteria used for this study: a) Country of origin of the game and languages it supports, b) Pedagogical intent, c) Individual or interaction with others, d) Guides/aids available, e) Recipients of the game, f) Results, and g) Gaming strategies. The games that were chosen had been used previously during the last decade (2009-2019) for training university faculty. Findings reveal that educational games facilitate changes in attitude and behavior, enable pedagogical innovation, enhance interaction with others, promote research, facilitate the acquisition of technological competencies and skills, and encourage respect and promotes awareness about social, ethical and legal use of ICTs. Aside from being innovative and interactive, games promote research and help maximize digital skills acquisition among teachers in different areas of knowledge.